Towards a New Generation of Passive Optical Net-works - Aguas Martinez, Elkin Fabián; Puerto Leguizamón, Gustavo Adolfo; Suárez Fajardo, Carlos Arturo (Ingeniería, 2016)
Context: Growth in bandwidth demand has boosted the development of new techniques for the transmission of information in telecommunication networks. Passive Optical Networks (PON) are presented as an alternative to conventional networks based on copper. This paper proposes and assesses the performance of an optical access network with TDM-WDM and wired-wireless convergence. Method: A teletraffic study was performed using a discrete event simulator. A simulation scenario was set up in order to obtain the packet loss and throughput of an optical access network under different load values, percentage of ONUs demanded bandwidth and number of wavelengths. Results: As the number of wavelengths used to cope with the exceeding traffic demanded by users, the results show that packet loss tends to decrease and throughput tends to increase in the network. Conclusions: The behavior of the variables analyzed in the results shows that when dimensioning a channel wavelength, which is required to determine the amount of resources needed to meet the bandwidth demand of the users, the proposed model positively influences the network behavior.